Cancer mortality differences among urban and rural residents in Lithuania - Kurtinaitis Juozas; Smailyte Giedre (BMC, 2008)
Abstract Background The aim of this study was to describe and to compare the cancer mortality rates in urban and rural residents in Lithuania. Methods Cancer mortality has been studied using the materials of the Lithuanian cancer registry. For the period 1993-2004 age-standardized urban and rural population mortality rates (World standard) were calculated for all malignant neoplasm's and for stomach, colorectal, lung, prostate, breast and cervical cancers. The annual percentage change (APC) was calculated using log-linear regression model, two-sided Mantel-Haenzel test was used to evaluate differences in cancer mortality among rural and urban populations. Results For males in rural population cancer mortality was higher than in urban (212.2 and 197.0 cases per 100000) and for females cancer mortality was higher in urban population (103.5 and 94.2 cases per 100000, p < 0.05). During the study period the age-standardized mortality rates decreased in both sexes in urban residents. The decreasing mortality trend in urban population was contributed by decline of the rates of lung and stomach cancer in male and breast, stomach and colorectal cancer in female. Mortality rates in both urban and rural population were increasing for prostate and cervical cancers. Conclusion This study shows that large rural and urban inequalities in cancer mortality exist in Lithuania. The contrast between the health of residents in urban and rural areas invites researchers for research projects to develop, implement, and enhance cancer prevention and early detection intervention strategies for rural populations.